MMP12, Lung Function, and COPD in High-Risk Populations - Hunninghake, Gary M; Cho, Michael H; Tesfaigzi, Yohannes; Soto-Quiros, Manuel E; Avila, Lydiana; Lasky-Su, Jessica; Stidley, Chris; Melén, Erik; Söderhäll, Cilla; Hallberg, Jenny; Kull, Inger; Kere, Juha; et al. (The New England journal of medicine, 2009)
A variant of MMP12, encoding a matrix metallopeptidase, is associated with increased lung function in children with asthma and in adult smokers. It is also associated with a decreased risk of chronic obstructive pulmonary disease in adult smokers. A variant of MMP12 is associated with increased lung function in children with asthma and in adult smokers. It is also associated with a decreased risk of chronic obstructive pulmonary disease in adult smokers. MMP-12 (matrix metalloproteinase 12, also known as macrophage metalloelastase or matrix metallopeptidase 12 [Mmp12] in mice) is produced by macrophages, the predominant cell type that patrols the lower airspaces under normal conditions and the main inflammatory cell type that is recruited with smoking. 1 Mmp12 is essential for the development of emphysema in mice exposed to cigarette smoke, 2 including mice with increased expression of interleukin-13. 3 Increased expression of MMP12 in the lower airways can lead to degradation of elastin, resulting in elastin fragments that can cause a positive feedback loop, further increasing macrophage recruitment in mice 4 and in cultured human cells. . . .